2004
DOI: 10.1007/s00423-003-0444-9
|View full text |Cite
|
Sign up to set email alerts
|

Validity of intra-operative neuromonitoring signals in thyroid surgery

Abstract: For intra-operative neuromonitoring, indirect stimulation of the RLN is superior to direct stimulation. An intact acoustic IONM signal is highly predictive of intact postoperative RLN function. When the IONM signal is abnormal or absent, a one-stage extensive thyroid resection should be performed only if the surgeon is absolutely convinced that the first RLN is not harmed or a total thyroidectomy is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
1
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 18 publications
7
160
1
11
Order By: Relevance
“…Similarly in our study, while there was no significant difference between the two groups in terms of RLN paralysis, the duration of operation in the group with nerve monitoring was significantly shorter. Even though some studies report that nerve dissection using IONM reduces the rate of permanent nerve damage following surgery [11][12][13][14], there is no consensus on this subject [15][16][17]. As the results of our study support us, we clinically suppose that nerve monitoring does not provide any contribution to an experienced surgeon; however, it might be used to assist less experienced surgeons with anatomical identification.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similarly in our study, while there was no significant difference between the two groups in terms of RLN paralysis, the duration of operation in the group with nerve monitoring was significantly shorter. Even though some studies report that nerve dissection using IONM reduces the rate of permanent nerve damage following surgery [11][12][13][14], there is no consensus on this subject [15][16][17]. As the results of our study support us, we clinically suppose that nerve monitoring does not provide any contribution to an experienced surgeon; however, it might be used to assist less experienced surgeons with anatomical identification.…”
Section: Discussionsupporting
confidence: 64%
“…During surgery, methods such as the palpation of cricothyroid muscle synchronous with the nerve impulse, observation of the movement of vocal cords by using direct or fiberoptic nasopharyngoscopy, measurement of the pressure on the endotracheal tube exerted by the movement of vocal cords, placement of electrodes on the vocal cord muscles, and formation of contact between the vocal cord mucosa and the electrodes placed on the surface of the endotracheal tube are performed [7][8][9][10]. Whereas in some studies, it has been reported that nerve dissection using intraoperative nerve monitoring (IONM) reduces the rate of permanent nerve damage following surgery [11][12][13][14], there is no consensus on this subject [15][16][17]. This study aims to compare and contrast the effects of two different technical approaches-visual identification of RLN combined with IONM and no RLN identification-on RLN damage in total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies conclude that IONM can be reliably used to predict normal cord function where nerve signal is intact and therefore has a high negative predictive value, on the order of 92-100%. 4,14,61 This is particularly the case when the identified nerve responds to less than 0.5 mA of stimulation. 62 Conversely, little information is gained when the IONM signal is lost/absent.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…Intraoperative loss of signal may indicate nerve injury or incorrect electrode placement/ equipment failure; it is therefore strongly suggested that IONM not be used as the sole method of RLN identification and preservation. 4,14,55,57,61,63 There is a lack of high-level evidence (i.e. level A, randomized control trials) to elucidate the true RLN sparing effect of IONM.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…Irrespective of the operative strategy of a 1-way or 2-way approach, the ipsilateral RLN (R2) and vagal stimulation (V2) after the completion of all operative measures serve for the detection of the RLN function and the prediction of a postoperatively intact or injured vocal fold function (3,(13)(14)(15)(16)(17)(18)(19)(20)(21). In post-resection intact VN signal and EMG, intact VC mobility can be assumed in more than 99% of the cases ( Table 3).…”
Section: Post-resectional Vagal Nerve Stimulation (V2) Recurrent Stimentioning
confidence: 99%